Treatment of Clubfoot Using the Ponseti Method - Dietz, Frederick R. (JBJS Essent Surg Tech, 2016)
The Ponseti method consists of a specific technique of manipulation of the clubfoot deformity, followed by the application of a plaster cast with the foot in the corrected position. A percutaneous tenotomy of the Achilles tendon is done prior to the final cast to gain complete correction in most patients. Bracing with a foot abduction orthosis is necessary to minimize relapse of the deformity. The method begins with the Ponseti manipulation and consists of the following steps: (1) Identify the head of the talus by palpation. (2) Supinate the forefoot to eliminate the cavus deformity and create a normal-appearing arch. (3) Abduct the forefoot with the vector of force parallel to the sole of the foot while using the lateral head of the talus as the fulcrum and maintaining the reduction of the cavus deformity. (4) This manipulation is followed by the application of an above-the-knee cast with the foot in the corrected position. (5) The manipulation and casting steps are repeated every 5 to 7 days until the foot is abducted approximately 50° from the frontal plane of the tibia. (6) In most patients (60% to >90%), a percutaneous tenotomy of the Achilles tendon is necessary to correct the residual ankle equinus after gaining full abduction of the foot with the manipulations. (7) The final cast is applied and worn for three weeks. (8) After removal of the final cast, the patient is managed with bracing with a foot abduction orthosis for 23 hours per day for 3 months. Bracing at night and during nap time is recommended until the child is 4 to 5 years old. The cavus deformity is eliminated after the application of 2 or 3 casts by the simple positioning maneuver. Abduction of the forefoot in the plane of the sole of the foot while using the head of the talus as the fulcrum results in the correction of the midfoot adduction deformity simultaneously with the hindfoot varus and the subtalar component of the equinus deformity. After full abduction is obtained, the cavus, adduction, and subtalar varus and equinus deformities are all completely corrected. The only residual deformity is the ankle equinus. Most feet require a percutaneous tenotomy to fully correct the ankle component of the equinus. The tenotomy can be performed as an outpatient procedure under local anesthetic without the need for sedation. If the foot can be dorsiflexed to >15° (without midfoot breach), a tenotomy is unnecessary. This manipulation allows complete correction of almost all idiopathic clubfeet in 4 to 7 sessions. Long-term follow-up (mean, 34 years; range, 25 to 42 years) has shown that clubfeet treated with the Ponseti method function as well as normal feet with respect to pain and level of activity.